Multidimensional Factors Can Explain the Clinical Worsening in People With Parkinson's Disease During the COVID-19 Pandemic: A Multicenter Cross-Sectional Trial - Silva-Batista C. (2021)
© Copyright © 2021 Silva-Batista, Coelho, Júnior, Almeida, Guimarães, Nóbrega, Machado Sanchez, Lindquist, Israel, Kanegusuku, Guimarães, Beckmann Bosaipo, Barbosa, Correa, Finatto, Mendes and Piemonte.Background: Self-reported clinical worsening by people with Parkinson's disease (PD) during social distancing may be aggravated in Brazil, where the e/tele-health system is precarious. Objectives: This study aims to investigate self-reported changes in motor and non-motor aspects during social distancing in people with PD living in Brazil and to investigate the factors that might explain these changes. Methods: In this multicenter cross-sectional trial, 478 people with a diagnosis of idiopathic PD (mean age = 67, SD = 9.5; 167 female) were recruited from 14 centers distributed throughout the five geographical regions of Brazil. The evaluators from each center applied a questionnaire by telephone, which included questions (previous and current period of social distancing) about the motor and non-motor experiences of daily living, quality of life, daily routine, and physical activity volume. Results: Self-reported clinical worsening in non-motor and motor aspects of daily life experiences (Movement Disorder Society-Unified PD Rating Scale—parts IB and II—emotional and mental health, and fear of falling) and in the quality of life was observed. Only 31% of the participants reported a guided home-based physical activity with distance supervision. Perceived changes in the quality of life, freezing of gait, decreased physical activity volume, daily routine, and fear of falling explained the self-reported clinical worsening (P < 0.05). Conclusions: Self-reported clinical worsening in people with PD living in Brazil during social distancing can also be aggravated by the precarious e/tele-health system, as perception of decreased physical activity volume and impoverishment in daily routine were some of the explanatory factors. Considering the multifaceted worsening, the implementation of a remote multi-professional support for these people is urgent.